The Impact of Green Supply Chain Management on Firm Competitiveness - Arman Marhamati; Iman Azizi (International Journal of Supply Chain Management, 2017)
This study was conducted to investigate the effect of green supply chain management on green performance and firm competitiveness in Shiraz Industrial Estate. Data were collected from 110 executives and managers in companies on the Estate using a pre-designed questionnaire. A descriptive, correlational methodology was adopted Data were analysed using structural equation modeling and partial least squares (PLS) path analysis. The results showed that: the internal green practices of a company have a positive and significant impact on external green collaboration; internal green practices and external green collaboration have a positive and significant impact on the company's green performance; and internal green practices, external green collaboration and the company's green performance have a positive and significant effect on firm competitiveness. Overall, the results suggest that strengthening green supply chain management improves green performance, which in turn increases firm competitiveness.